Exclusively oral manifestation of secondary syphilis - Paiva, João Paulo Gonçalves de; Medeiros, Nathassia Emanuely de; Calone, Iris Sawazaki (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Introduction: Syphilis is at an epidemic level in the Brazilian public health and it occurs, mainly, in the genital region. However, about 5% of the syphilitic lesions are oral. Objective: To report a clinical case of secondary syphilis with exclusively manifestation in the oral cavity. Case report: A 32-yearold woman who attended the Dentistry Clinic of the Universidade Estadual do Oeste do Paraná (UNIOESTE) complaining of “sores in the mouth”. Physical examination revealed a number of ulcerated, pseudomembranous and painful lesions at apex, lateral border, belly, floor and lingual frenulum. After the diagnostic hypothesis of syphilis was raised, serological tests for human immunodeficiency virus (HIV) 1, HIV-2, Venereal Disease Research Laboratory (VDRL) and complete blood count were requested. With the positivity up to the 1/32 titration of the VDRL examination, the patient was referred to the Parasitic Infectious Diseases Center of Cascavel, where a general physical examination and antibiotic therapy with benzathine penicillin were carried out. Subsequent to the drug treatment, the patient returned to the UNIOESTE Dentistry Clinic, where the total remission of the lesions was observed, confirming the diagnosis of secondary syphilis exclusively in the mouth. Conclusion: This report illustrates the importance of each phase of the disease, noting that in some cases the manifestations of the infection may be solely oral, with the dentist having a notable role in the diagnosis and reference to the adequate treatment, and the responsibility to control the necessary diagnostic procedures.